Hubungan Aktivitas Fisik dengan Kejadian Dismenore Pada Remaja Putri Kelas X di MAN 1 Sleman - Widiawati, Fera; Ismarwati, Ismarwati; Mahmudah, Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the relationship between physical activity and the incidence of dysmenorrhea among 10th-grade female students at MAN 1 Sleman. This research is correlational with a cross-sectional approach, aiming to analyze the relationship between the independent variable (physical activity) and the dependent variable (incidence of dysmenorrhea). The study population consisted of all 10th-grade female students at MAN 1 Sleman, totaling 119 individuals with a sample size of 101 students. Sampling was conducted using purposive sampling techniques based on inclusion and exclusion criteria. Primary data were collected using the Numerical Rating Scale (NRS) to measure the severity of dysmenorrhea and the Global Physical Activity Questionnaire (GPAQ) from WHO in 2014 to assess the level of physical activity. Data analysis was performed using the Spearman Rank statistical test. The results showed that respondents with moderate physical activity mostly experienced mild dysmenorrhea, with 19 respondents (40.4%). The p-value of 0.035 (< α 0.05) indicates a significant relationship between physical activity and the incidence of dysmenorrhea among these female students.